2016
DOI: 10.1002/ijop.12383
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, psychosocial and physical health correlates of common mental disorder symptoms among mothers in Trinidad and Tobago: Examining ethnic variations

Abstract: Historical and cultural experiences have shaped the life experiences of cultural communities in Trinidad and Tobago. Using a cultural focus, the goal of this investigation was to examine ethnic variations both in the prevalence of common mental disorder (CMD) symptoms as well as in the associations between sociodemographic, psychosocial, physical health correlates and CMDs among mothers in Trinidad and Tobago. Participants included 1002 mothers (359 African-, 353 Indo- and 290 Mixed-Ethnic Trinidadian). Mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(30 reference statements)
0
1
1
Order By: Relevance
“…Many authors reported that women experience poorer mental well-being than men do and that it is negatively correlated to children's number. The latter result is in contradiction with ours (49) (50). A 26-European-country study showed evidence of lower prevalence of good mental wellbeing among women.…”
Section: Mental Health Determinants In Academic Physicianscontrasting
confidence: 99%
See 1 more Smart Citation
“…Many authors reported that women experience poorer mental well-being than men do and that it is negatively correlated to children's number. The latter result is in contradiction with ours (49) (50). A 26-European-country study showed evidence of lower prevalence of good mental wellbeing among women.…”
Section: Mental Health Determinants In Academic Physicianscontrasting
confidence: 99%
“…69,70,71 Some authors suggest that impaired physical health makes people more vulnerable to common mental disorders. 50 In literature, many studies had confirmed the negative effect of workaholism on worker well-being. In fact, workaholic had a worse state of general health, more somatic symptoms, higher levels of anxiety/insomnia, social dysfunction and symptoms of depression.…”
Section: Mental Health Determinants In Academic Physiciansmentioning
confidence: 99%